Sex-specific modulation of juvenile social play by vasopressin - Veenema, Alexa H. (2013)
Social play activities among juveniles are thought to contribute to the development of social and emotional skills in humans and animals. Conversely, social play deficits are observed in developmental neuropsychiatric disorders. Importantly, many of these disorders show sex differences in incidence, course of the disease, and severity of symptoms. We hypothesized that sex differences in the neural systems controlling social behavior can contribute to these differences. We therefore studied the involvement of the sexually dimorphic vasopressin and oxytocin systems, which have been implicated in these disorders, in juvenile social play behavior. Single-housed 5-week-old juvenile male and female rats were exposed to an unknown age-and sex-matched conspecific for 10 min in their home cage and social play behaviors were recorded. We found no consistent sex differences in level or elements of social play in vehicle-treated rats. However, intracerebroventricular injection of the specific vasopressin 1a receptor (V1aR) antagonist (CH(2))(5)Tyr(Me(2)) AVP significantly reduced social play behaviors in males, while increasing them in females. Intracerebroventricular injection of the specific oxytocin receptor antagonist des-Gly-NH(2),d(CH(2))(5)[Tyr(Me)(2),Thr(4)]OVT did not alter social play in either sex. To locate the effects of V1aR blockade on social play, we targeted the lateral septum, a sexually dimorphic brain region showing denser vasopressin fibers in males than in females and abundant expression of V1aR in both sexes. Surprisingly, blockade of V1aR in the lateral septum increased social play behaviors in males, but decreased them in females. These findings suggest sex- and brain region-specific roles for vasopressin in the regulation of social play behavior in juvenile rats.